PENGELOLAAN DAN KEBIJAKAN PELESTARIAN KAWASAN HUTAN LINDUNG JOMPI DI KABUPATEN MUNA - La Ode Agus Salim Mando; Sitti Marwah; Aminuddin Mane Kandari; Safril Kasim; La Ode Midi; La Ode Siwi; Hafidah Nur; Anwar Sadad (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
This research aims to determine the realization of management and policies carried out in preserving the Jompi Protected Forest Area, Muna Regency. The research was carried out in June - July 2021, where the basic method of this research was descriptive analytical qualitative. Data was collected using observation and interview methods. The research results show that: (1) The realization of management of the Jompi Protected Forest Area by the Muna Regency Forestry Service does not comply with applicable regulations and legislation, including: Law No. 41 of 1999 concerning Forestry, PP No. 44 of 2004 concerning Forestry Planning and Presidential Decree no. 32 of 1990 concerning Management of Protected Forest Areas, so it does not guarantee the implementation of sustainable management of the Jompi Protected Forest Area. Apart from that, there are still many violations committed by the community which further increase the escalation of forest destruction. (2) the policies that need to be implemented in the Jompi Protected Forest Area, Muna Regency are a) a more comprehensive planning and structuring design of the Forest Area involving various elements, including central, regional government, non-governmental organizations (NGOs) and the community, b) organizational structure good forest management unity supported by professional and adequate human resources, c) implementation of forest conservation, empowerment of communities around forest areas, so that they do not depend on protected forests for their livelihoods, d) intensive socialization of conservation of Jompi protected forest areas both through print and online media , as well as through study and discussion forums.